A conceptual ontological framework for managing the social business process to enhance customer experience. (6th September 2020) - Helmy, Yehia M.; Abdelgaber, Sayed; Fahmy, Hanan; Montasser, Hend S.
Abstract : Nowadays, organizations strive for business process optimization to survive the current competitive business environment. The widespread use of social media and Web 2.0 applications has dramatically changed the structure of the business process. Such evolution caused an increase in the flow of data and information, which led to knowledge‐intensive business processes. Thus, modeling the knowledge‐intensive processes became essential to make use of the flow of knowledge from social media and to fulfill their demanding requirements. Therefore, knowledge and social dimensions should be integrated into the traditional business process life cycle. This integration yields a large flow of customer knowledge that needs to be efficiently used and managed. Moreover, the use of ontologies for knowledge representation opens up a supplementary view for providing machine‐accessible terminology to processes. Ontologies make a significant contribution to the categorization and organization of the incorporated and unstructured information. This paper proposes a framework that integrates the social business processes with a knowledge base in the form of an ontology to manage and enhance the overall customer experience. The proposed framework aims to enable organizations to improve knowledge support for their customer‐driven business processes. In addition, the extracted knowledge from social media will support organizations in managing the customer knowledge and building up the relationships with customers. The proposed social ontology will ease the querying of existing customer knowledge and inferring new knowledge that enhances optimizing the business process, and customer experience.